Iron and Noncontrast Magnetic Resonance T2* as a Marker of Intraplaque Iron in Human Atherosclerosis - Winner, Marshall W. (2014)
OBJECTIVE: Iron has been implicated in atherogenesis and plaque destabilization, while less is known regarding iron-related proteins in this disease. We compared ex vivo quantities to in vivo vessel wall T2*, which is a noncontrast magnetic resonance relaxation time that quantitatively shortens with increased tissue iron content. We also tested the hypothesis that carotid atherosclerosis patients have abnormal T2* times vs. controls that would help support a role for iron in human atherosclerosis. METHODS AND RESULTS: 46 patients undergoing carotid endarterectomy and 14 subjects without carotid disease were prospectively enrolled to undergo carotid MRI. Ex vivo measurements were performed on explanted plaque and 17 mammary artery samples. Plaques vs. normal arteries had higher levels of ferritin (median = 7.3 [IQR=4 – 13.8] vs. 1.0 [0.6 – 1.3] ng/mg, P < .001) and oxidized low-density lipoprotein (0.17 [0.12 – 0.30] vs. 0.01 [0.003 – 0.03] ng/mg, P < .001) as well as hepcidin (8.7 [4.6 – 12.4] vs. 2.6 [1.3 – 7.0] ng/mL, P = .03); serum hepcidin levels did not distinguish atherosclerosis patients from controls (40.6 [18.8 – 88.6] vs. 33.9 [17.6 – 55.2], P = 0.42). Shorter in vivo T2* paralleled larger plaque volume (ρ = −.44, p = 0.01), and diseased arteries had shorter T2* values compared to controls (17.7 ± 4.3 vs. 23.0 ± 2.4 ms, P < .001). CONCLUSIONS: Diseased arteries have greater levels of iron-related proteins ex vivo and shorter T2* times in vivo. Further studies should help define T2*'s role as a biomarker of iron and atherosclerosis.